Multi Open-/Short-Circuit Fault-Tolerance Using Modified SVM Technique for Three-Level HANPC Converters - Halabi, Laith M.; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2021)
Open- and short-circuit faults are the most severe issues that affect the stability and reliability of power conversion systems. The space vector modulation (SVM) technique is widely used to control power converters. However, conventional SVM is incapable of controlling the system effectively when such faults occur. Considering these, this article proposes a modified SVM that is capable of tolerating the extreme cases of faults (including multi open-/short-circuit faults) simultaneously. An innovative fault tolerance method is proposed to tolerate multifaults in hybrid active neutral point converters (HANPCs). Furthermore, new voltage reference signals are created in addition to calculating voltage offset and inserting modified switching sequences. A descriptive performance analysis of the modified SVM technique is applied under healthy and faulty conditions. Correspondingly, the effects of the total harmonic distortion of the system performance are also highlighted and explained. The results reveal that the proposed control strategy can effectively maintain healthy and safe operation under faulty conditions without the need for additional parts or alteration of the topology configuration. In addition, the proposed method can be applied to HANPCs without special requirements to withstand high voltage levels. The effectiveness of the proposed method is verified by simulation and experimental results.
Keywords: Control strategies; Performance analysis; Power conversion systems; Short-circuit fault; Space vector modulations (SVM); Stability and reliabilities; Topology configurations; Total harmonic distortion (THD); Fault tolerance; hybrid active neutral point clamped converters; multifaults; open-circuit; short-circuit